Polyelectrolyte and secondary battery
Patent Information
- Application Number
- JP2024110667
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-06-21
- Filing Date
- 2024-07-10
- Publication Date
- 2025-02-17
AI Technical Summary
【0011】 本開示の少なくとも一つの態様によれば、高温下においても機械的強度が高く、かつ、高いイオン導電率を有し、かつ、ポリマー電解質と電池負極との界面におけるデンドライトの発生を抑制しうるポリマー電解質を得ることができる。また、本開示の少なくとも一つの態様は、高温環境下においても高い耐衝撃性を有し、かつ、優れた電池性能を有する二次電池を得ることができる。
Smart Images

Figure 2025023821000038 
Figure 2025023821000039 
Figure 2025023821000040
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a polymer electrolyte and a secondary battery. [Background technology]
[0002] In recent years, with the development of portable devices such as tablet computers and smartphones, and electric vehicles, the demand for secondary batteries as their power source is expanding. Secondary batteries are generally composed of electrodes (positive and negative electrodes) and an electrolyte, and charge and discharge are performed by the movement of ions between the electrodes via the electrolyte. Such secondary batteries are used in a wide range of applications, from small devices such as mobile phones to large devices such as electric vehicles. Therefore, high safety and further improvement in performance are required.
[0003] In order to further improve the safety of secondary batteries, development of solid-state secondary batteries in which the conventional flammable electrolyte is replaced with a solid electrolyte is underway. Sulfide-based, oxide-based, and polymer-based materials are being widely investigated as solid electrolytes. In order to improve the charge-discharge characteristics of secondary batteries, it is generally important to enlarge the interface between the active material in the electrode and the electrolyte. Here, the active material is a material involved in the reaction that generates electricity. Although sulfide-based and oxide-based solid electrolytes have excellent ionic conductivity, it is difficult to enlarge the interface with the active material and they may not have sufficient impact resistance. Therefore, it has been proposed to use flexible solid electrolytes such as gel electrolytes that combine electrolyte and polymers.
[0004] Patent Document 1 describes a gel electrolyte containing polyether and an ionic liquid. Patent Document 2 describes a gel electrolyte in which a quaternary ammonium base is incorporated into the main chain to improve affinity with the electrolyte. Patent Document 3 describes a dry polymer electrolyte containing glyme and a lithium salt. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-090677 A [Patent Document 2] International Publication No. 2004 / 027789 [Patent Document 3] JP 2009-104891 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, lithium ion secondary batteries are required to have higher charge and discharge characteristics in addition to higher safety. When a polymer gel such as that in Patent Documents 1 and 2 is used as an electrolyte, the strength at high temperatures decreases, and there is a risk of short circuit due to impact. In addition, in a dry polymer system such as that in Patent Document 3, in order to exhibit high ionic conductivity, it is necessary to form a complex of lithium ions with glyme, which is an organic solvent. It is known that lithium salts coordinated with glyme become ionic liquids, and potentially have the same problems as liquid electrolytes. Furthermore, in secondary batteries, dendrites (dendrites) may occur at the interface between the electrolyte and the metal negative electrode, which may shorten the cycle life. Among the negative electrode materials for secondary batteries, "metal negative electrodes" have the highest charge capacity density, and their practical use is expected from the viewpoint of improving energy density. Since it is believed that the mastery of the use of metal negative electrodes will greatly improve the performance of secondary batteries, it is important to suppress the occurrence of dendrites. Furthermore, as the growth of dendrites progresses, there is a risk that the base material and packaging materials that make up the battery may be damaged, raising safety concerns. There are also concerns about the impact.
[0007] Therefore, -Even at high temperatures, the deterioration of impact resistance and the risk of short circuits are suppressed. -Excellent ionic conductivity, -Long cycle life Polymer electrolytes are desirable.
[0008] At least one aspect of the present disclosure is directed to a polymer electrolyte that has high mechanical strength and high ionic conductivity even at high temperatures and can suppress the generation of dendrites at the interface between the polymer electrolyte and a battery negative electrode. Also, at least one aspect of the present disclosure is directed to providing a secondary battery that has high impact resistance and excellent battery performance even in a high-temperature environment. [Means for solving the problem]
[0009] According to at least one embodiment of the present disclosure, there is provided a polymer electrolyte comprising: The polymer electrolyte includes a polymer and an alkali metal salt, The alkali metal salt includes an alkali metal salt having at least one anion selected from the group consisting of bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and hexafluorophosphate; The polymer is A structure represented by the following formula (1), At least one structure selected from the group consisting of a structure represented by the following formula (2) and a structure represented by the following formula (3), and a structure represented by the following formula (4): When the total number of moles of the anions in the alkali metal salt contained per unit mass of the polymer electrolyte is A and the number of moles of the sulfonylimide groups bonded to the polymer is B, A and B satisfy the relationship of the following formula (X): 0.50≦A / (A+B) (X) In addition, the polymer electrolyte has a volume swelling ratio of 30 to 120% as measured by a methyl ethyl ketone immersion method. [ka] (In formula (1), R 1 R represents a hydrogen atom or a methyl group. 2 R represents a linear or branched alkylene group having 1 to 6 carbon atoms. 3represents an alkyl group having 1 to 6 carbon atoms. In formula (2), R 4 R each independently represents a hydrogen atom or a methyl group. 5 and R 6 each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. In formula (3), R 7 R each independently represents a hydrogen atom or a methyl group. 8 , R 9 and R 10 R each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. 11 represents a trivalent organic group having 1 to 6 carbon atoms. In the formulas (1) to (3), A1, B1, D1, D2 and D3 each independently represent at least (-CH 2 CH 2 It is a linking group having an ethylene oxide structure represented by the formula: [ka] (In formula (4), R 12 R represents a hydrogen atom or a methyl group. 13 R represents a divalent linking group. 14 represents a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms. + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion. The sulfonylimide group is a functional group represented by the following formula (S). [ka] In formula (S), R represents a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms.
[0010] Also, according to at least one embodiment of the present disclosure, there is provided a secondary battery including a positive electrode, a bulk electrolyte, and a negative electrode, wherein at least one of the positive electrode, the bulk electrolyte, and the negative electrode contains the above-mentioned polymer electrolyte. Effect of the Invention
[0011] According to at least one aspect of the present disclosure, it is possible to obtain a polymer electrolyte that has high mechanical strength and high ionic conductivity even at high temperatures, and that can suppress the generation of dendrites at the interface between the polymer electrolyte and the battery negative electrode. In addition, at least one aspect of the present disclosure can obtain a secondary battery that has high impact resistance even in a high-temperature environment and has excellent battery performance. [Brief description of the drawings]
[0012] [Figure 1] Schematic cross-sectional view of a secondary battery using the polymer electrolyte of the present disclosure as a bulk electrolyte. [Diagram 2] Schematic cross-sectional view of a secondary battery using the polymer electrolyte of the present disclosure as a binder for a positive electrode active material. [Diagram 3] 1 is a schematic cross-sectional view of a secondary battery using the polymer electrolyte of the present disclosure as a positive electrode active material binder, a bulk electrolyte, and a negative electrode active material binder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including the lower limit and upper limit, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. In addition, when XX is a group, multiple XXs may be selected, and the same applies to YY and ZZ.
[0014] The present inventors have conducted extensive research in order to obtain a polymer electrolyte that has high mechanical strength even at high temperatures, high ionic conductivity, and suppresses the generation of dendrites at the interface between the polymer electrolyte and the battery negative electrode. First, the inventors discovered that it is possible to increase ionic conductivity by using a polyether-modified (meth)acrylic resin that has a special three-dimensional crosslinked structure in a dry polymer system in which promotion of lithium ion mobility by a liquid electrolyte cannot be expected.
[0015] The present inventors have further studied the polyether-modified (meth)acrylic resin. As a result, they have found that the polyether-modified (meth)acrylic resin is modified by bonding an anionic functional group having at least one selected from the group consisting of a fluorinated sulfonylimide (FSI) group and a perfluoroalkylsulfonylimide (PFSI) group to the molecular chain of the polyether-modified (meth)acrylic resin, and by bonding a specific cation X as a counter ion (cation) of the anionic functional group. + It has been found that by combining the above, a polymer electrolyte can be obtained that can achieve high ionic conductivity and an increased transport number of the specific cation even at low temperatures.
[0016] That is, the polymer electrolyte of the present disclosure satisfies the following conditions. The three-dimensional crosslinked structure of the polymer has many free chains at one end that are not bonded to the polymer chain (structure of formula (1)), resulting in a very low crosslink density (volume swelling ratio). The three-dimensional crosslinked structure of the polymer has an anionic functional group having a fluorinated sulfonylimide group or a perfluoroalkylsulfonylimide group and a cation (the structure of formula (2) and / or (3), and the structure of formula (4)). The polymer electrolyte contains a polymer having the above-mentioned anionic functional group in the molecule and an alkali metal salt, which is an electrolyte (supporting electrolyte) that is not fixed to the polymer, in a specific ratio (formula (X)), which can suppress the generation of dendrites.
[0017] The present inventors speculate as follows why the polymer electrolyte according to one embodiment of the present disclosure has high ionic conductivity without relying on a liquid electrolyte. In dry polymer systems, where ions such as lithium ions cannot be stabilized by liquid electrolytes, the ions move between polymer chains that are undergoing molecular motion. Therefore, polymer systems that are three-dimensionally cross-linked to suppress the risk of short circuits due to deformation of the membrane at high temperatures are more susceptible to steric hindrance than liquid systems.
[0018] However, the polymer used in the present disclosure has a three-dimensional crosslinked structure (the structure of formula (2) and / or (3)) and is not easily deformed even at high temperatures. On the other hand, the polymer has a terminal free chain (the structure of formula (1)) in which one end is not bonded to other polymer chains. This is thought to prevent the polymer from forming a dense mesh structure, making it less likely to inhibit ion movement while maintaining strength.
[0019] Furthermore, the fluorinated sulfonylimide structure or perfluoroalkylsulfonylimide structure bonded to the polymer can make it difficult to inhibit the movement of ions, and an electrolyte with a high ion transport number can be provided.
[0020] Furthermore, the fluorinated sulfonylimide structure or perfluoroalkylsulfonylimide structure bonded to the polymer suppresses stereoregularity and reduces the crystallinity of the polymer, which is believed to suppress the decrease in ionic conductivity at low temperatures.
[0021] In addition, the anionic group having a fluorinated sulfonylimide structure or a perfluoroalkylsulfonylimide structure and the cation (structure of formula (4)) bonded to the polymer make the polymer highly polar. Therefore, even in a system in which a supporting electrolyte such as a lithium salt is added, the supporting electrolyte is not precipitated and the amount of the supporting electrolyte that can be dissolved can be increased.
[0022] In addition, by using an alkali metal salt as a supporting electrolyte, it is possible to suppress the local increase in the concentration of ions such as lithium ions near the metal negative electrode. This is thought to be because free anions, which have a higher dissociation rate than the immobilized anions, move through the polymer, suppressing the interaction between the immobilized anionic groups and ions, and leveling out the concentration of ions. In particular, the presence of free anions in the range that satisfies the formula (X): 0.50 ≦ A / (A + B) described below can suppress the localization of ions.
[0023] The growth of dendrites is caused by localized concentration of ions such as lithium ions in an electrolyte. Therefore, delocalizing the distribution of ions suppresses the generation of dendrites and leads to an extension of the cycle life of the secondary battery. The polymer used in the present disclosure is designed to have a very low crosslinking density, so that free anions can easily move. Since free anions are easily mobile, it is believed that the effect of delocalizing the ion distribution can be more significantly exerted.
[0024] The three-dimensional crosslinked structure of the polymer has many free chains at one end that are not bonded to the polymer chain, and the crosslink density is very low. This is clearly shown by the volume swelling ratio of the polymer electrolyte measured by the methyl ethyl ketone immersion method. Specifically, the volume swelling ratio of the polymer electrolyte using methyl ethyl ketone (MEK) is 30 to 120%.
[0025] The volume swelling ratio is the ratio of the volume of a three-dimensional cross-linked polymer before and after it is immersed in a specific solvent and swells to saturation due to the solvent. The volume swelling ratio is calculated using the following formula, where the volume of the test specimen is calculated from the weight in air and the weight in water. The specific measurement method will be described later. Volume swelling rate (%) = (volume when saturated with solvent due to swelling) / (volume before solvent immersion) × 100
[0026] A volume swelling ratio of less than 30% for a polymer electrolyte is considered to indicate that there are few free terminal chains (the structure of formula (1)) and many three-dimensional cross-linked structures. This leads to low ionic conductivity and low rate characteristics of the secondary battery. In addition, because there are many three-dimensional cross-linked structures, it is difficult to obtain the effect of delocalizing the ion distribution, and dendrites are generated. On the other hand, a volume swelling ratio of the polymer electrolyte exceeding 120% indicates a lack of a three-dimensional cross-linked structure, which is likely to result in a decrease in strength, such as a decrease in impact resistance at high temperatures. The volume swelling ratio of the polymer electrolyte is preferably from 40 to 120%, more preferably from 60 to 110%, and further preferably from 70 to 105%.
[0027] Preferred embodiments of the present disclosure will be described in detail below with reference to the drawings. The components, materials, shapes, relative arrangements, etc. described in these embodiments do not limit the scope of the present disclosure.
[0028] (1) Secondary battery type The secondary battery comprises a positive electrode, a bulk electrolyte, and a negative electrode, and at least one of the positive electrode, the bulk electrolyte, and the negative electrode contains the polymer electrolyte of the present disclosure. For example, the bulk electrolyte is a polymer electrolyte. An example of a secondary battery using the polymer electrolyte of the present disclosure is shown in Figures 1 to 3. The secondary battery 1 shown in Figure 1 shows an example of a schematic configuration of a secondary battery using a polymer electrolyte as a bulk electrolyte 7. A positive electrode active material 3 provided on a positive electrode current collector 2 is fixed by a positive electrode active material binder 4 to form a positive electrode 6. The positive electrode 6 may contain a conductive assistant 5.
[0029] A negative electrode active material 8 provided on a negative electrode current collector 9 forms a negative electrode 10. In Fig. 1, the negative electrode active material represents metallic lithium, indium, etc. A bulk electrolyte 7 is provided between the positive electrode 6 and the negative electrode 10.
[0030] The secondary battery 1 shown in FIG. 2 shows an example of a schematic configuration of a secondary battery using a polymer electrolyte as a positive electrode active material binder 4. In the embodiment of FIG. 2, a positive electrode 6 contains a polymer electrolyte. For example, the positive electrode 6 has a positive electrode active material 3 and a positive electrode active material binder 4 that fixes the positive electrode active material, and the positive electrode active material binder 4 is the polymer electrolyte of the present disclosure. In the configuration of FIG. 2, a bulk electrolyte 7 represents an oxide-based or sulfide-based inorganic solid electrolyte. The other configurations are the same as those of FIG. 1.
[0031] The secondary battery 1 shown in FIG. 3 shows an example of a schematic configuration of a secondary battery using a polymer electrolyte as a positive electrode active material binder 4, a bulk electrolyte 7, and a negative electrode active material binder 11. In the embodiment of FIG. 3, the positive electrode, the bulk electrolyte, and the negative electrode contain a polymer electrolyte. That is, the positive electrode 6 has a positive electrode active material 3 and a positive electrode active material binder 4 that fixes the positive electrode active material, and the positive electrode active material binder 4 is the polymer electrolyte of the present disclosure. In addition, the bulk electrolyte 7 is the polymer electrolyte of the present disclosure. In addition, the negative electrode 10 has a negative electrode active material 8 and a negative electrode active material binder 11 that fixes the negative electrode active material 8, and the negative electrode active material binder 11 is the polymer electrolyte of the present disclosure. In the configuration of FIG. 3, the negative electrode active material 8 represents a carbon material such as graphite. The other configurations are the same as those of FIG. 1.
[0032] In order to more effectively achieve the effects of the present disclosure, as shown in FIGS. 1 and 3, it is preferable that the bulk electrolyte 7 is a polymer electrolyte that permeates the positive electrode active material 3 and the negative electrode active material 8 to increase the contact area.
[0033] (Method of manufacturing solid secondary batteries) The solid secondary battery can be fabricated by known cell fabrication techniques such as laminate cell type, coin cell type, pressurized cell type, etc. The laminate cell type will be described below as an example.
[0034] A laminate is obtained in which a positive electrode, a bulk electrolyte, and a negative electrode are arranged between a positive electrode current collector and a negative electrode current collector. Electrode tabs are welded to the positive electrode and negative electrode current collectors. A laminate in which a positive electrode current collector, a positive electrode, a bulk electrolyte, a negative electrode, and a negative electrode current collector are laminated in this order is wrapped in an aluminum laminate film and sealed while reducing the pressure with a vacuum packaging machine. The end of the electrode tab is exposed outside the laminate film, and the tab and the aluminum laminate film are sealed in a state where they are bonded by thermocompression. After sealing, if necessary, pressure may be applied using an isostatic pressure pressurizing device or the like. The bulk electrolyte may be a solid electrolyte or a polymer electrolyte, and both may be used for lamination. In addition to the above laminate, other layers such as an elastic material or a resin material may be laminated in the aluminum laminate film for the purpose of strength, molding, etc. Also, a bipolar type in which a plurality of laminates are laminated may be used.
[0035] (Positive electrode current collector) The positive electrode current collector may be, for example, a metal foil. Examples of the metal include aluminum, stainless steel, copper, silver, gold, platinum, nickel, and palladium. One type may be used alone, or two or more types may be used in combination.
[0036] (Cathode active material) As the positive electrode active material, for example, a material commonly used in secondary batteries such as lithium ion secondary batteries can be used. For example, (CF) m , (C 2 F) m , MnO 2 , TiS 2 , MoS 2 , FeS 2 , Li xA Chief of Staff 2 , Li xA NiO 2 , Li xA MnO 2 , Li xA Co y Ni 1-y O 2 , Li xA Co y M 1-y O z , Li xA Ni1-y M y O z , Li xB Mn 2 O 4 , Li xB Mn 2-y M y O 4 (In each of the above formulas, M represents at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B; xA=0 to 1.2, xB=0 to 2.0, y=0 to 0.9, and z=2.0 to 2.3), vanadium oxides and lithium compounds thereof, niobium oxides and lithium compounds thereof, conjugated polymers using organic conductive substances, and olivine compounds. In addition, the xA value and the xB value in each of the above composition formulas are values before the start of charging and discharging, and increase or decrease due to charging and discharging. The positive electrode active material can be used alone or in combination of two or more kinds.
[0037] (Conductive assistant) The conductive auxiliary material may be any material commonly used in secondary batteries such as lithium ion secondary batteries. Examples of the conductive auxiliary material include graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, conductive fibers such as carbon fibers and metal fibers, metal powders such as aluminum powder, conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene derivatives. The conductive auxiliary material may be used alone or in combination of two or more.
[0038] (Active material binder) The active material binder may be one commonly used in secondary batteries such as lithium ion secondary batteries, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, carboxymethyl cellulose, etc.
[0039] The polymer electrolyte of the present disclosure may be used as a bulk electrolyte, a positive electrode active material binder, a negative electrode active material binder, or may be used as a bulk electrolyte, a positive electrode active material binder, and a negative electrode active material binder. That is, it is preferable that the secondary battery satisfies at least one of the following (i) to (iii). (i) The positive electrode 6 has a positive electrode active material 3 and a positive electrode active material binder 4 that fixes the positive electrode active material, and the positive electrode active material binder 4 is the polymer electrolyte of the present disclosure. (ii) Bulk electrolyte 7 is a polymer electrolyte of the present disclosure. (iii) Negative electrode 10 has negative electrode active material 8 and negative electrode active material binder 11 that fixes the negative electrode active material 8, and negative electrode active material binder 11 is the polymer electrolyte of the present disclosure.
[0040] It is particularly preferable to use the polymer electrolyte of the present disclosure as the positive electrode active material binder, since lithium ions can easily reach from the surface to the deep part of the positive electrode 6. The active material binder may be used alone or in combination of two or more kinds.
[0041] The positive electrode 6 can be produced, for example, by pressing a positive electrode mixture onto the surface of the positive electrode current collector 2, or by applying a positive electrode mixture slurry, drying, and further rolling as necessary to form the positive electrode 6. It can also be prepared by kneading a positive electrode active material, a conductive assistant, and a positive electrode active material binder. The positive electrode mixture slurry can also be prepared, for example, by dissolving or dispersing the positive electrode active material, the conductive assistant, and the active material binder in a medium such as dehydrated N-methyl-2-pyrrolidone, acetonitrile, methyl ethyl ketone, or ethylene glycol ethers.
[0042] (Negative electrode current collector) The negative electrode current collector may be, for example, a metal foil. Examples of metals include aluminum, stainless steel, copper, silver, gold, platinum, nickel, and palladium. The metals may be used alone or in combination of two or more.
[0043] (Negative electrode active material) Examples of the negative electrode active material include metals, metal fibers, carbon materials, oxides, nitrides, silicon, silicon compounds, tin, tin compounds, various alloy materials, etc. Among these, from the viewpoint of capacity density, metals, oxides, carbon materials, silicon, silicon compounds, tin, tin compounds, etc. are preferred.
[0044] Examples of metals include metallic Li and In-Li, and examples of oxides include Li 4 Ti 5 O 12 (LTO: lithium titanate). Examples of carbon materials include various natural graphites, coke, partially graphitized carbon, carbon fiber, spherical carbon, various artificial graphites, and amorphous carbon. Examples of silicon compounds include silicon-containing alloys, silicon-containing inorganic compounds, silicon-containing organic compounds, and solid solutions. Examples of tin compounds include SnO B (0 <B<2)、SnO 2 , SnSiO 3 , Ni 2 Sn 4 , Mg 2 Examples include Sn.
[0045] The negative electrode material may also contain a conductive assistant. Examples of the conductive assistant include graphite such as natural graphite and artificial graphite, and carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black. When a polymer electrolyte is used as a bulk electrolyte, graphite is particularly suitable for use as the negative electrode active material.
[0046] Examples of the conductive assistant include conductive fibers such as carbon fibers, carbon nanotubes, and metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene dielectrics.
[0047] (solid electrolyte) In secondary batteries, solid electrolytes are sometimes used as bulk electrolytes that are arranged between the positive and negative electrodes as a lithium ion migration layer and also function as separators, and can also be used as auxiliary agents to improve the conductivity of lithium ions by being mixed into the active material layers of the positive and negative electrodes.
[0048] The polymer electrolyte of the present disclosure can be suitably used as either a bulk electrolyte or an auxiliary material, which can increase the contact interface between the bulk electrolyte and the positive and negative electrode active materials, and has flexibility that can follow the expansion and contraction of the positive and negative electrode active materials, thereby improving the characteristics of the secondary battery.
[0049] In addition, by using the polymer electrolyte of the present disclosure as a bulk electrolyte, the effect of suppressing dendrites is easily exhibited. Therefore, when the bulk electrolyte is the polymer electrolyte of the present disclosure, It is preferred.
[0050] The bulk electrolyte and auxiliary material may be a solid electrolyte other than a polymer electrolyte, such as an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or a complex hydride-based solid electrolyte. The oxide-based solid electrolyte is Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 Or Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 Nasicon-type compounds such as Li 6.25 LA 3 ZR 2 Al 0.25 O 12 Garnet-type compounds such as Li 0.33 Li 0.55 TiO 3 Perovskite-type compounds such as Li 14 Zn(GeO 4 ) 4 Lithium-type compounds such as Li 3 PO 4 Or Li 4 SiO 4 , Li 3 BO 3 Examples of sulfide-based solid electrolytes include Li 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , LiI-Li 2 SP 2 S 5 , LiI-Li 2 SP 2 O 5 , LiI-Li 3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 etc. The solid electrolyte may be crystalline or amorphous, or may be glass ceramics. 2 SP 2 S 5 Such statements are made by Li 2 S and P 2 S 5 The sulfide-based solid electrolyte refers to a sulfide-based solid electrolyte formed using raw materials containing the above.
[0051] The polymer electrolyte of the present disclosure can be used as a bulk electrolyte, a positive electrode active material binder, or a negative electrode active material binder. Hereinafter, the configuration of the polymer electrolyte according to one embodiment of the present disclosure will be described in detail.
[0052] The polymer electrolyte of the present disclosure is preferably a solid electrolyte or a semi-solid electrolyte, such as a dry polymer electrolyte or a gel electrolyte. That is, a non-liquid electrolyte is preferable. More preferably, it is a dry polymer electrolyte. The polymer electrolyte is preferably substantially free of liquid components, such as a liquid electrolyte.
[0053] <Polymer electrolyte> The polymer electrolyte according to an embodiment of the present disclosure has a polymer having the following structure: The polymer is, for example, a (meth)acrylic polymer. The polymer electrolyte is, for example, a polyether acrylic resin having a three-dimensional crosslinked structure having the following structure: The structure represented by formula (1) At least one structure selected from the group consisting of a structure represented by formula (2) and a structure represented by formula (3) The structure represented by formula (4)
[0054] The polymer electrolyte has a structure represented by the following formula (1). [ka]
[0055] In formula (1), R 1 R represents a hydrogen atom or a methyl group. 2R represents a linear or branched alkylene group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 2 to 4). 3 represents an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 1). A1 in the formula (1) is at least an ethylene oxide represented by (-CH2CH2-O-). It is a linking group having an oxide structure.
[0056] The structure represented by formula (1) is preferably a structure represented by the following formula (1-1). [ka] In formula (1-1), R 1 R represents a hydrogen atom or a methyl group. 2 R represents a linear or branched alkylene group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 2 to 4). 3 represents an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 1). m1 and n1 each represent the average number of moles added, where m1 represents an integer of 1 or more (preferably 1 to 110, more preferably 13 to 46), and n1 represents an integer of 0 or more (preferably 5% to 25% of m1, more preferably 11% to 25% of m1).
[0057] The polymer electrolyte has at least one structure selected from the group consisting of the structure represented by the following formula (2) and the structure represented by the following formula (3). At least one structure selected from the group consisting of the structure represented by the formula (2) and the structure represented by the formula (3) may be the structure represented by the formula (2). This structure can form a three-dimensional crosslinked structure. [ka]
[0058] In formula (2), R 4 R each independently represents a hydrogen atom or a methyl group. 5 , R6 each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 2 to 4). In formula (3), R 7 R each independently represents a hydrogen atom or a methyl group. 8 , R 9 , R 10 R each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 2 to 4). 11 represents a trivalent organic group having 1 to 6 carbon atoms (preferably 1 to 3, more preferably 1).
[0059] In formulae (2) and (3), B1, D1, D2 and D3 each independently represent a linking group having at least an ethylene oxide structure represented by (-CH2CH2-O-). In the formulas (1) to (3), it is preferable that A1, B1, D1, D2 and D3 each independently further have a propylene oxide structure represented by (-CH2CH(CH3)-O-). The arrangement of the ethylene oxide structure and the propylene oxide structure may be a block copolymer or a random copolymer. It is preferable that it is a random copolymer. Furthermore, A1, B1, D1, D2 and D3 may each independently further contain a diol structure having 1 to 6 carbon atoms (preferably 4 to 6) to the extent that the effect of the present disclosure is not impaired. x -O-, R x is an alkylene group having 1 to 6 carbon atoms (preferably 4 to 6).
[0060] The structure represented by formula (2) is preferably a structure represented by the following formula (2-1). [ka]
[0061] In formula (2-1), R 4 R each independently represents a hydrogen atom or a methyl group. 5 , R 6each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 2 to 4). m2 and n2 represent the average number of moles added, m2 represents an integer of 1 or more (preferably 1 to 110, more preferably 13 to 46), and n2 represents an integer of 0 or more (preferably 5% to 25% of m2, more preferably 11% to 25% of m2).
[0062] The chain sandwiched between the two -COO- may further contain a diol structure having 1 to 6 carbon atoms (preferably 4 to 6 carbon atoms) to the extent that the effect of the present disclosure is not impaired. For example, a diol structure may be contained between ethylene oxide structures, between propylene oxide structures, or between an ethylene oxide structure and a propylene oxide structure. The diol structure is -OR x -O-, R x is an alkylene group having 1 to 6 carbon atoms (preferably 4 to 6).
[0063] The structure represented by formula (3) is preferably a structure represented by the following formula (3-1). [ka]
[0064] In formula (3-1), R 7 R each independently represents a hydrogen atom or a methyl group. 8 , R 9 , R 10 R each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 2 to 4). 11 represents a trivalent organic group (preferably a hydrocarbon group) having 1 to 6 carbon atoms (preferably 1 to 3, more preferably 1). m3 and n3 are the average number of moles added, each m3 independently represents an integer of 1 or more (preferably 1 to 110, more preferably 13 to 46), and each n3 independently represents an integer of 0 or more (preferably 5% to 25% of m3, more preferably 11% to 25% of m3).
[0065] -COO- and R to the extent that the effect of the present disclosure is not impaired. 11The chain sandwiched between the ethylene oxide and propylene oxide structures may further contain a diol structure having 1 to 6 carbon atoms (preferably 4 to 6 carbon atoms). A diol structure may be included between the structure. The diol structure is -OR x -O-, R x is an alkylene group having 1 to 6 carbon atoms (preferably 4 to 6).
[0066] The average number of moles Meo of ethylene oxide structures added per mole of (meth)acryloyl residue in the polymer contained in the polymer electrolyte is preferably 2.5 moles or more. More preferably, Meo is 13 to 46. Within the above range, the crosslink density of the polymer main chain becomes more appropriate, so that high lithium ion conductivity can be obtained while maintaining strength at high temperatures. The (meth)acryloyl residue is a form in which a (meth)acryloyl group is addition polymerized, and is represented by the following structure in formula (1), for example. [ka]
[0067] In addition, in the polymer contained in the polymer electrolyte, the average number of moles Mpo of propylene oxide structures added per mole of (meth)acryloyl residues is preferably 5 to 25% of the average number of moles Meo of ethylene oxide structures added per mole of (meth)acryloyl residues, and more preferably 11 to 25%. By being in the above range, the crystallinity of the polymer main chain is suppressed even if the molecular weight between crosslinking points is large, and it becomes easier to suppress the inhibition of lithium ion migration, particularly at low temperatures.
[0068] The average added mole numbers Meo and Mpo can be measured by decomposing the polymer electrolyte using pyrolysis GC / MS, and quantifying the fragments derived from the (meth)acryloyl residues, the fragments derived from the ethylene oxide structure, and the fragments derived from the propylene oxide structure by creating respective calibration curves. The average number of moles added, Mpo, is preferably 1-15, and more preferably 2-10.
[0069] In the polymer electrolyte of the present disclosure, the three-dimensional crosslinked structure of the polymer has a very low crosslink density as described above, and the polymer chain has many free chains at one end that are not bonded to other polymer chains, etc. Such a crosslinked structure can be obtained, for example, by reacting the following materials. Polyether mono(meth)acrylate At least one selected from the group consisting of polyether di(meth)acrylate and polyether tri(meth)acrylate Compounds having an unsaturated reactive functional group, an anionic functional group having a fluorinated sulfonylimide group or a perfluoroalkylsulfonylimide group, and a cation (hereinafter also referred to as "fluorine sulfonylimide-based ionic compounds")
[0070] (Polyether mono(meth)acrylate) The polyether mono(meth)acrylate can form a structure represented by formula (1) (preferably formula (1-1)). As the polyether mono(meth)acrylate, for example, at least one selected from the group consisting of polyethylene glycol mono(meth)acrylate and mono(meth)acrylate of polyethylene glycol-propylene glycol copolymer can be used. When the mono(meth)acrylate of polyethylene glycol-propylene glycol copolymer is used, the structure is represented by the following formula: ethylene glycol structure: propylene glycol structure The molar ratio of the above is preferably from 100:0 to 50:50, and more preferably from 80:20 to 95:5.
[0071] When the molar ratio of the ethylene glycol structure:propylene glycol structure is within this range, the lithium ion transportability of the polyethylene glycol can be maintained at a high level, and in combination with the structure of formula (4), the inhibition of lithium ion migration caused by the crystallization of the polymer can be more easily suppressed.
[0072] The polyether mono(meth)acrylate is represented, for example, by the following formula (1'). [ka] In formula (1'), R 1 , R 2 , R 3 , m1 and n1 are the same as in formula (1-1).
[0073] (Polyether di(meth)acrylate) The polyether di(meth)acrylate can form a structure represented by formula (2) (preferably formula (2-1)). As the polyether di(meth)acrylate, for example, at least one selected from the group consisting of polyethylene glycol di(meth)acrylate and di(meth)acrylate of polyethylene glycol-propylene glycol copolymer can be used. When di(meth)acrylate of polyethylene glycol-propylene glycol copolymer is used, the molar ratio of ethylene glycol structure:propylene glycol structure is preferably 100:0 to 50:50, more preferably 80:20 to 95:5.
[0074] When the molar ratio of the ethylene glycol structure:propylene glycol structure is within this range, the transportability of ions such as lithium ions by polyethylene glycol can be maintained at a high level, and in combination with the structure of formula (4), it becomes easier to suppress the inhibition of the movement of ions such as lithium ions due to crystallization of the polymer.
[0075] Polyether di(meth)acrylate is represented, for example, by the following formula (2'). [ka] In formula (2'), R 4 , R 5 , R 6 , m2 and n2 are the same as in formula (2-1).
[0076] The chain sandwiched between the two -COO- may further contain a diol structure having 1 to 6 carbon atoms (preferably 4 to 6) to the extent that the effect of the present disclosure is not impaired. For example, a diol structure may be contained between ethylene oxide structures, between propylene oxide structures, or between an ethylene oxide structure and a propylene oxide structure. The diol structure is represented by -O-Rx-O-, where Rx is an alkylene group having 1 to 6 carbon atoms (preferably 4 to 6).
[0077] (Polyether tri(meth)acrylate) The polyether tri(meth)acrylate can form a structure represented by formula (3) (preferably formula (3-1)). As the polyether tri(meth)acrylate, for example, at least one selected from the group consisting of polyethylene glycol tri(meth)acrylate and tri(meth)acrylate of polyethylene glycol-propylene glycol copolymer can be used. When the tri(meth)acrylate of polyethylene glycol-propylene glycol copolymer is used, the molar ratio of ethylene glycol structure:propylene glycol structure is preferably 100:0 to 50:50, more preferably 80:20 to 95:5.
[0078] When the molar ratio of the ethylene glycol structure:propylene glycol structure is within this range, the transportability of ions such as lithium ions by polyethylene glycol can be maintained at a high level, and in combination with the structure of formula (4), inhibition of the movement of ions such as lithium ions due to crystallization of the polymer can be more easily suppressed.
[0079] Polyether tri(meth)acrylate is represented, for example, by the following formula (3'). [ka]
[0080] In formula (3'), R 7 , R 8 , R9 , R 10 , R 11 , m3 and n3 are the same as in formula (3-1). -COO- and R to the extent that the effect of the present disclosure is not impaired. 11 The chain sandwiched between the -OR may further contain a diol structure having 1 to 6 carbon atoms (preferably 4 to 6). For example, a diol structure may be contained between the ethylene oxide structure and the propylene oxide structure. The diol structure is represented by the formula: x -O-, R x is an alkylene group having 1 to 6 carbon atoms (preferably 4 to 6).
[0081] Formula (1), Formula (2) and Formula (3) (preferably Formula (1-1), Formula (2-1) and Formula (3) The structure represented by -1) can be obtained, for example, by using a polyether polyol obtained by ring-opening polymerization of ethylene oxide and propylene oxide. In addition, in the formulas (1-1), (2-1), and (3-1) (and the formulas (1'), (2'), and (3')), (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the propylene oxide structure represented by (a)-O-) may be a block copolymer or a random copolymer, preferably a random copolymer.
[0082] The mass content of the structure represented by formula (1) in the polymer contained in the polymer electrolyte is represented by α. The mass content of the structure represented by formula (2) and the structure represented by formula (3) in the polymer is represented by β (preferably the content of the structure represented by formula (2)). The mass ratio of α to β, α:β, is preferably 70:30 to 98:2, more preferably 88:12 to 96:4, and further preferably 90:10 to 95:5.
[0083] The mass ratio α:β can be adjusted by specifically adjusting the ratio of polyether mono(meth)acrylate to polyether di(meth)acrylate and / or tri(meth)acrylate. When the mass ratio α:β is within the above range, the polymer does not have an excessively dense network structure, and the strength is maintained while the movement of lithium ions is less likely to be hindered, which is particularly preferable.
[0084] In the polymer electrolyte, it is preferable that m1+n1 in formula (1-1) is 1 to 110 (more preferably 14 to 58), and m2+n2 in formula (2-1) and / or m3+n3 in formula (3-1) (preferably m2+n2 and m3+n3) are 1 to 110 (more preferably 14 to 58). By being in the above range, the crosslink density of the polymer main chain becomes appropriate, so that the ionic conductivity of the polymer electrolyte is higher while maintaining the strength at high temperatures, and the rate characteristics of the secondary battery are also improved.
[0085] In the polymer electrolyte, it is preferred that m1:n1 in formula (1-1) is 80:20 to 95:5 (more preferably 80:20 to 90:10), and m2:n2 in formula (2-1) and / or m3:n3 in formula (3-1) (preferably m2:n2 in formula (2-1) and m3:n3 in formula (3-1)) are 80:20 to 95:5 (more preferably 85:15 to 95:5). Within the above range, the crystallinity of the polymer main chain is suppressed even if the molecular weight between crosslinking points is large, and inhibition of lithium ion migration, particularly at low temperatures, is more easily suppressed.
[0086] <Fluorine sulfonylimide anion group> The polymer in the polymer electrolyte is characterized by having a structure represented by the following formula (4). [ka] In formula (4), R 12 R represents a hydrogen atom or a methyl group. 13R represents a divalent linking group. 14 represents a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms (preferably 1 to 2). + represents a cation, and represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion.
[0087] R 13 The divalent linking group in the formula (I) preferably contains a linear or branched alkylene group having 1 to 7 carbon atoms (preferably 2 to 4 carbon atoms). 30 -(wherein the carbonyl group is R 12 is preferably bonded to the carbon atom to which R is bonded. 30 is preferably a linear or branched alkylene group having 1 to 7 carbon atoms (preferably 2 to 4 carbon atoms).
[0088] The polyether composition of polyether (meth)acrylates, which are the main components of the polymer, is preferably polyethylene glycol in terms of the transportability of ions such as lithium ions. However, polyethylene glycol has high crystallinity, and in order to suppress crystallization, especially in the low temperature range, there is a method of copolymerizing a propylene glycol structure, which has poor ion transportability, at a certain ratio. As a result, it is difficult to achieve high ionic conductivity only with the polyether composition having the structure of formulas (1) to (3).
[0089] On the other hand, since the structure of formula (4) is an anion structure with a relatively large molecular size, the crystallinity can be reduced by introducing the structure of formula (4) into the polymer structure. Therefore, in the polyether composition, crystallization at low temperatures can be suppressed even if the amount of propylene glycol structure, which has poor lithium ion transport properties, is reduced. As a result, it is possible to maintain high ionic conductivity even at low temperatures.
[0090] The content of the structure represented by formula (4) in the polymer is preferably 1 to 25 parts by mass, more preferably 1 to 10 parts by mass, and even more preferably 1 to 5 parts by mass, relative to 100 parts by mass in total of the structures represented by formulas (1), (2), and (3). When the content of formula (4) is within this range, it is possible to expect an improvement in ionic conductivity due to a decrease in crystallinity while containing a sufficient amount of ions. The state after these reactions can be confirmed by analysis using known means such as combustion ion chromatography, pyrolysis GC / MS, FT-IR, and NMR.
[0091] <Cation> Cation X shown in formula (4) + The cation may be at least one selected from the group consisting of lithium ions, sodium ions, and potassium ions. The cation may be selected according to the carrier in the secondary battery. For example, lithium is selected for a lithium ion secondary battery using lithium cobalt oxide or the like as the positive electrode active material, and sodium is selected for a sodium-sulfur secondary battery.
[0092] <Supporting electrolyte> The polymer electrolyte contains an alkali metal salt. The alkali metal salt can be a supporting electrolyte. The alkali metal salt contains an alkali metal salt having at least one anion selected from the group consisting of bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and hexafluorophosphate. The alkali metal salts having the specific anions have a high dissociation rate, and therefore the polymer electrolyte using these can obtain excellent ionic conductivity.
[0093] The alkali metal salt is preferably at least one selected from the group consisting of lithium salts, sodium salts, and potassium salts. For example, in the case of lithium salts, LiN(CF 3 SO 2 ) 2 , LiN(SO 2 F) 2 , LiPF6 At least one selected from the group consisting of:
[0094] The total number of moles of anions in the alkali metal salt contained per unit mass of the polymer electrolyte, i.e., bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and hexafluorophosphate, is designated as A. Also, the number of moles of sulfonylimide groups bonded to the polymer is designated as B. In this case, A and B satisfy the relationship of the following formula (X). 0.50≦A / (A+B) (X) As mentioned above, satisfying formula (X) indicates the presence of many free anions, which can suppress ion localization. If A / (A+B) is less than 0.50, the effect of suppressing ion localization cannot be obtained, and dendrites will occur.
[0095] The sulfonylimide group is represented by the following formula (S). [ka]
[0096] In formula (S), R represents a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms (preferably 1 to 2). It is preferable that A and B satisfy 0.65≦A / (A+B)≦0.96. The content of the alkali metal salt is preferably 5 parts by mass or more and 25 parts by mass or less per 100 parts by mass of the polymer in the polymer electrolyte. When A / (A+B) and the content of the supporting electrolyte are within the above ranges, the alkali metal salt is well compatible with the polymer and does not precipitate, and high ionic conductivity is obtained without significantly decreasing the transport number of ions, and the generation of dendrites can be further suppressed.
[0097] The polymer electrolyte may contain other supporting electrolytes in addition to the above-mentioned alkali metal salts, so long as the effect of the present disclosure is not impaired. For example, other lithium salts include LiBF 4 , LiN(SO2 C 2 F 5 ) 2 , LiAlCl 4 , LiSBF 6 , LiSCN, LiCF 3 SO 3 , LiAsF 6 , LiClO 4 , lower aliphatic lithium carboxylate, LiCl, LiBR, and LiI. The lithium salt may be used alone or in combination of two or more. As the sodium salt and potassium salt, there can be mentioned those in which the lithium in the above lithium salts is replaced by sodium or potassium.
[0098] The state of the anions in the polymer electrolyte, that is, A and B, can be confirmed by analysis using known means such as LC / MS, NMR, and GPC.
[0099] <Liquid electrolyte, electrolyte> The polymer electrolyte may contain a liquid electrolyte or an electrolytic solution, for example, an ionic liquid or a non-aqueous electrolytic solution, as long as the effects of the present disclosure are not impaired and safety in high temperature ranges is not impaired.
[0100] Specific examples of ionic liquids include the following combinations of cations and anions: can be done. The cation may be at least one selected from the group consisting of quaternary ammonium, imidazolium, pyridinium, pyrrolidinium, and piperidinium. The anion may be at least one selected from the group consisting of a fluoroalkylsulfonylimide anion, a fluorosulfonylimide anion, a fluoroalkylsulfonate anion, a fluorosulfonate anion, a fluoroalkylcarboxylate anion, a fluoroalkylmethide anion, a fluoroborate anion, a fluorophosphate anion, a dicyanamide anion, a thiocyanate anion, a bisoxalatoborate anion, a perchlorate anion, and derivatives thereof.
[0101] The non-aqueous electrolyte is, for example, a liquid in which about 1 mole of lithium salt is dissolved in a non-aqueous solvent. Examples of the non-aqueous solvent include ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Examples of the lithium salt include LiPF 6 , LiBF 4 , LiClO 4 etc.
[0102] In some cases, the ionic conductivity of a polymer electrolyte can be improved by including a liquid electrolyte. However, in order to avoid a decrease in mechanical strength at high temperatures, the amount of liquid electrolyte is preferably, for example, 10 parts by mass or less, 5 parts by mass or less, 1 part by mass or less, or 0.5 parts by mass or less per 100 parts by mass of the polymer included in the polymer electrolyte.
[0103] The polymer electrolyte may contain a non-conductive filler such as silica, quartz powder, titanium oxide, zinc oxide, and calcium carbonate, if necessary. By adding these non-conductive fillers to the paint for forming the electrolyte layer, they function as a film-forming assistant when the paint is coated in the process of forming the electrolyte layer. The content of such non-conductive fillers is preferably 0.1 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the polymer forming the electrolyte layer.
[0104] The polymer electrolyte may contain a conductive filler as necessary, as long as the effect of the present disclosure is not impaired. As the conductive filler, conductive fine particles such as carbon black, zinc oxide, tin oxide, and titanium oxide can be used. In particular, when the polymer electrolyte is used as a binder for a positive or negative electrode active material, the polymer electrolyte contains a conductive filler, which can reduce the internal resistance of the secondary battery. The content of the conductive filler is preferably 0.5 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the polymer contained in the polymer electrolyte.
[0105] The polymer electrolyte is preferably a cured product of an electrolyte solution. The electrolyte solution may be, for example, a mixture of the following materials: Polyether mono(meth)acrylate At least one selected from the group consisting of polyether di(meth)acrylate and polyether tri(meth)acrylate At least one compound selected from the group consisting of compounds having an unsaturated reactive functional group, an anionic functional group having a fluorinated sulfonylimide group or a perfluoroalkylsulfonylimide group, and a cation If necessary, the electrolyte solution may contain a known polymerization initiator, such as a photopolymerization initiator, or a known organic solvent, such as methyl ethyl ketone.
[0106] (Method of forming a polymer electrolyte layer) The method for forming the polymer electrolyte layer is not particularly limited. For example, the above-mentioned polymer electrolyte materials are mixed by a known method to form a polymer electrolyte layer. The electrolyte solution is applied by a known application method such as bar coating, spin coating, or roll coating, and then the polymer material contained in the electrolyte solution is polymerized by a known means such as UV to form a polymer electrolyte layer. The polymer electrolyte layer can be formed at a desired position such as on a positive electrode or a negative electrode. The thickness of the polymer electrolyte layer serving as the bulk electrolyte is preferably 5.0 μm or more and 100.0 μm or less. EXAMPLES
[0107] Specific examples and comparative examples according to the present disclosure are described below. However, the present disclosure is not limited to the following examples and comparative examples.
[0108] First, polyether acrylates that form the structures represented by formula (1) and formula (2) were synthesized. A synthesis example of a polyether monoacrylate that can form the structure represented by formula (1) is shown below. <Synthesis of polyether monoacrylate> (Polyether monoacrylate A-1) 15.5 parts by mass of 1-hexanol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Laboratory Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 1041 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 8:2 was continuously introduced over 260 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 180 minutes until the pressure inside the container became 0.2 MPa or less. After that, the temperature was raised to 130°C over 30 minutes, and stirring was carried out until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90° C. for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. The alkali adsorbent was then removed by filtration, and the mixture was dried under reduced pressure at 130° C. to obtain a polyether monool having Mn of 6000.
[0109] Next, 100 parts by mass of the obtained polyether monol, 1.26 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 2.02 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.08 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 5 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature and washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-1.
[0110] (Polyether monoacrylate A-2) 18.6 parts by mass of 1-hexanol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Laboratory Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure in the system was reduced to -0.1 MPa at 100°C, and 976 parts by mass of a gas mixture of ethylene oxide / propylene oxide = 95:5 in molar fraction was continuously introduced over 240 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 180 minutes until the pressure inside the container became 0.2 MPa or less. After that, the temperature was raised to 130°C over 30 minutes, and stirring was carried out until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90° C. for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. The alkali adsorbent was then removed by filtration, and the mixture was dried under reduced pressure at 130° C. to obtain a polyether monool having Mn of 5000.
[0111] Next, 100 parts by mass of the obtained polyether monol, 1.51 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 2.42 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.08 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 5 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-2.
[0112] (Polyether monoacrylate A-3) Polyether monoacrylate A-3 was obtained in the same manner as for Polyether monoacrylate A-2, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 8:2.
[0113] (Polyether monoacrylate A-4) 33.7 parts by mass of 1-butanol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Research Institute Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 984 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 8:2 was continuously introduced over 240 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 150 minutes until the pressure inside the container became 0.2 MPa or less. The temperature was then raised to 130°C over 30 minutes, and the mixture was stirred until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90°C for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (Kyowa Chemical Industry Co., Ltd.) was added and the mixture was stirred for another 30 minutes. Next, the alkaline adsorbent was removed by filtration, and the residue was dried under reduced pressure at 130°C to obtain a polyether monol having Mn of 2000.
[0114] Next, 100 parts by mass of the obtained polyether monol, 3.78 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 6.05 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-4.
[0115] (Polyether monoacrylate A-5) 67.4 parts by mass of 1-butanol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Research Institute Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 946 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 8:2 was continuously introduced over 240 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 130 minutes until the pressure inside the container became 0.2 MPa or less. The temperature was then raised to 130°C over 30 minutes, and the mixture was stirred until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90°C for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (Kyowa Chemical Industry Co., Ltd.) was added and the mixture was stirred for another 30 minutes. Next, the alkaline adsorbent was removed by filtration, and the residue was dried under reduced pressure at 130°C to obtain a polyether monol having Mn of 1000.
[0116] Next, 100 parts by mass of the obtained polyether monool and 7 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.) were mixed together. A Dean-Stark reactor equipped with a stirrer was charged with 0.56 parts by mass of toluene, 12.1 parts by mass of paratoluenesulfonic acid (Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene. The mixture was heated and stirred at 115°C and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-5.
[0117] (Polyether monoacrylate A-6) 169 parts by mass of 1-butanol (Tokyo Chemical Industry Co., Ltd.) and 8 parts by mass of potassium hydroxide (Kojundo Chemical Research Institute Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 927 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 8:2 was continuously introduced over 220 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 120 minutes until the pressure inside the container became 0.2 MPa or less. The temperature was then raised to 130°C over 30 minutes, and the mixture was stirred until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90°C for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (Kyowa Chemical Industry Co., Ltd.) was added and the mixture was stirred for another 30 minutes. Next, the alkaline adsorbent was removed by filtration, and the residue was dried under reduced pressure at 130°C to obtain a polyether monol having Mn of 400.
[0118] Next, 100 parts by mass of the obtained polyether monol, 18.9 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 24.2 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-6.
[0119] (Polyether monoacrylate A-7) Polyether monoacrylate A-7 was obtained in the same manner as in the preparation of polyether monoacrylate A-5, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 5:5.
[0120] (Polyether monomethacrylate A-8) 112 parts by mass of 1-butanol (Tokyo Chemical Industry Co., Ltd.) and 5 parts by mass of potassium hydroxide (Kojundo Chemical Research Institute Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 937 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 5:5 was continuously introduced over 240 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 120 minutes until the pressure inside the container became 0.2 MPa or less. The temperature was then raised to 130°C over 30 minutes, and the mixture was stirred until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90°C for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (Kyowa Chemical Industry Co., Ltd.) was added and the mixture was stirred for another 30 minutes. Next, the alkaline adsorbent was removed by filtration, and the residue was dried under reduced pressure at 130°C to obtain a polyether monol having Mn of 600.
[0121] Next, 100 parts by mass of the obtained polyether monool, 15.0 parts by mass of methacrylic acid (manufactured by Mitsubishi Gas Chemical Company, Inc.), 20.2 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.11 parts by mass of hydroquinone (Tokyo Chemical Industry Co., Ltd.) and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monomethacrylate A-8.
[0122] (Polyether monomethacrylate A-9) A polyether monool having Mn 400 was obtained in the same manner as in the preparation of polyether monoacrylate A-6, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 5:5.
[0123] Next, 100 parts by mass of the obtained polyether monol, 22.6 parts by mass of methacrylic acid (manufactured by Mitsubishi Gas Chemical Co., Ltd.), 24.2 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monomethacrylate A-9. The resulting polyether mono(meth)acrylates are shown in Table 1.
[0124] Next, a synthesis example of a polyether diacrylate capable of forming the structure represented by formula (2) will be shown. <Synthesis of polyether diacrylate> (Polyether diacrylate B-1) 13.7 parts by mass of 1,4-butanediol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Laboratory Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 1041 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 8:2 was continuously introduced over 280 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 170 minutes until the pressure inside the container became 0.2 MPa or less. After that, the temperature was raised to 130°C over 30 minutes, and stirring was carried out until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer and stirred at 90°C for 30 minutes, and then 50 g of an alkali adsorbent Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. Next, the alkali adsorbent was removed by filtration, and the mixture was dried under reduced pressure at 130°C to obtain a polyether diol with Mn of 6000.
[0125] Next, 100 parts by mass of the obtained polyether diol, 2.52 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 2.02 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.08 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 5 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature and washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether diacrylate B-1.
[0126] (Polyether diacrylate B-2) A polyether diol having an Mn of 5000 was prepared in the same manner as polyether diacrylate B-1, except that the amount of 1,4-butanediol (manufactured by Tokyo Chemical Industry Co., Ltd.) was changed to 16.4 parts by mass. obtained.
[0127] Next, 100 parts by mass of the obtained polyether diol, 3.02 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 2.42 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.08 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C and reacted for 5 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature and washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether diacrylate B-2.
[0128] (Polyether diacrylate B-3) 41.0 parts by mass of 1,4-butanediol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Laboratory Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 955 parts by mass of a gas mixture of ethylene oxide / propylene oxide = 9:1 molar fraction was continuously introduced over 220 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 150 minutes until the pressure inside the container became 0.2 MPa or less. After that, the temperature was raised to 130°C over 30 minutes, and stirring was carried out until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer and stirred at 90°C for 30 minutes, and then 50 g of an alkali adsorbent Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. Next, the alkali adsorbent was removed by filtration, and the mixture was dried under reduced pressure at 130°C to obtain a polyether diol with Mn of 2000.
[0129] Next, 100 parts by mass of the obtained polyether diol, 7.56 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 6.05 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C and reacted for 5 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature and washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether diacrylate B-3.
[0130] (Polyether diacrylate B-4) 205 parts by mass of 1,4-butanediol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Laboratory Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 899 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 9:1 was continuously introduced over 210 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 110 minutes until the pressure inside the container became 0.2 MPa or less. After that, the temperature was raised to 130°C over 30 minutes, and stirring was carried out until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer and stirred at 90°C for 30 minutes, and then 50 g of an alkali adsorbent Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. Next, the alkali adsorbent was removed by filtration, and the mixture was dried under reduced pressure at 130°C to obtain a polyether diol with Mn of 400.
[0131] Next, 100 parts by mass of the obtained polyether diol, 37.8 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 24.2 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and the reaction product was The reaction was carried out for 6 hours while removing water from the system. The reaction solution was then cooled to room temperature and washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether diacrylate B-4.
[0132] (Polyether diacrylate B-5) Polyether diacrylate B-5 was obtained in the same manner as in the preparation of polyether diacrylate B-2, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 9:1.
[0133] (Polyether dimethacrylate B-6) A polyether diol having Mn 1000 was obtained in the same manner as in polyether diacrylate B-3, except that 1,4-butanediol (manufactured by Tokyo Chemical Industry Co., Ltd.) was used at 82.0 parts by mass and the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 5:5. Next, 100 parts by mass of the obtained polyether diol, 18.1 parts by mass of methacrylic acid (manufactured by Mitsubishi Gas Chemical Co., Ltd.), 12.1 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature and washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether diacrylate B-6.
[0134] The resulting polyether di(meth)acrylates are shown in Table 2. [Table 1] The polyether composition ratio is expressed as a mole fraction. EO represents ethylene oxide, and PO represents propylene oxide.
[0135] [Table 2] The polyether composition ratio is expressed as a mole fraction. EO represents ethylene oxide, and PO represents propylene oxide.
[0136] <Synthesis of reactive ionic compounds> (Synthesis of ionic compound C-1) 15.0g (0.06mol) of 3-Sulfopropyl Methacrylate Potassium Salt (Tokyo Chemical Industry Co., Ltd.) was suspended in 100mL of THF and 0.5mL of N,N-dimethylformamide, and then 20mL (0.28mol) of thionyl chloride was added and stirred for 3 hours. This was concentrated under reduced pressure, and the residue was dissolved in dichloromethane, washed with 50mL of pure water and 50mL of saline, and concentrated under reduced pressure again to obtain a pale yellow liquid. The resulting light yellow liquid was added to a solution of 9.20 g (0.06 mol) of trifluoromethanesulfonamide (Tokyo Chemical Industry Co., Ltd.) and 27.3 mL (0.20 mol) of triethylamine (Kishida Chemical Co., Ltd.) dissolved in 50 mL of tetrahydrofuran, and the mixture was stirred for 2 hours, after which the reaction solution was concentrated under reduced pressure. The resulting residue was dissolved in dichloromethane, washed with 150 mL of pure water, and the organic layer was dried under reduced pressure to obtain a yellow liquid. The resulting yellow liquid was dissolved in 300 mL of tetrahydrofuran, and 1.43 g (0.18 mol) of lithium hydride (Fujifilm Wako Pure Chemical Industries, Ltd.) was added and stirred overnight. Unreacted lithium hydride was filtered off using Celite filtration, and the filtrate was dried under reduced pressure to obtain ionic compound C-1.
[0137] (Synthesis of ionic compound C-2) Ion compound C-2 was obtained in the same manner as for ionic compound C-1, except that the starting material was changed to 15.9 g (0.06 mol) of 3-sulfopropyl acrylate potassium salt (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0138] (Synthesis of ionic compound C-3) Hydroxymethanesulfonate (Atomax Chemicals Products) 7.78g (0.07mol) was dissolved in THF 50mL, methacrylic acid (Kishida Chemicals) 5.17g (0.06mol) and molecular sieves were added, and the mixture was stirred at 80°C for 3 hours. The filtrate was filtered through Celite and dried under reduced pressure, then dissolved again in THF 50mL, potassium hydride (Merck) 2.41g (0.06mol) was added, and the mixture was stirred at room temperature for 2 hours. The white solid obtained after drying under reduced pressure was used as the starting material to obtain ionic compound C-3 in the same manner as ionic compound C-1.
[0139] (Synthesis of ionic compound C-4) 1-HEPTANESULFONYL CHLORIDE, 7-HYDROXY(H Add 12.9 g of ethyl amine (manufactured by Hong Kong Chemhere Products) and 6.07 g (0.06 mol) of triethylamine (manufactured by Kishida Chemical Co., Ltd.) to 80 mL of dichloromethane and stir at room temperature. After washing with 100 mL of pure water, the organic phase was dried under reduced pressure to obtain an oily liquid. 5.64 g (0.06 mol) of sodium acrylate (manufactured by Merck) was dissolved in 50 mL of ethanol, and the oily liquid obtained earlier and 0.022 g (0.20 mmol) of hydroquinone (manufactured by Kanto Chemical Co., Ltd.) were added and stirred at 70°C for 5 hours. The pale yellow solid obtained after drying under reduced pressure was used as the starting material to obtain ionic compound C-4 in the same manner as ionic compound C-2.
[0140] (Synthesis of ionic compound C-5) Ion compound C-5 was obtained in the same manner as for ionic compound C-2, except that the reactant was changed from trifluoromethanesulfonamide (Tokyo Chemical Industry Co., Ltd.) to 5.94 g (0.06 mol) of sulfamoyl fluoride (Atomax Chemicals Products).
[0141] (Synthesis of ionic compound C-6) Ionic compound C-6 was obtained in the same manner as for ionic compound C-1, except that the reactant was changed from trifluoromethanesulfonamide (Tokyo Chemical Industry Co., Ltd.) to 18.0 g (0.06 mol) of nonafluorobutane-1-sulfonamide (Enamine Co., Ltd.).
[0142] (Synthesis of ionic compound C-7) Ion compound C-7 was obtained in the same manner as ionic compound C-5, except that lithium hydride was changed to 4.32 g (0.18 mol) of sodium hydride (manufactured by Tokyo Chemical Industry Co., Ltd.) as the reactant.
[0143] (Synthesis of ionic compound C-8) Ion compound C-8 was obtained in the same manner as ionic compound C-6, except that lithium hydride was changed to 7.22 g (0.18 mol) of potassium hydride (Merck) as the reactant.
[0144] The chemical structures of the obtained reactive ion compounds are shown in formulas C-1 to C-8. [ka]
[0145] [ka]
[0146] <Preparation of electrolyte solution of polymer electrolyte> [Example 1] As materials for the polymer electrolyte, the following materials were mixed and stirred. Polyether monoacrylate NK Ester M-230G (manufactured by Shin-Nakamura Chemical Co., Ltd.): 50.0 parts by weight Polyether diacrylate B-1: 50.0 parts by mass Ionic compound C-3: 5.0 parts by mass Supporting electrolyte Li TFSI (lithium bis(trifluoromethanesulfonyl)imide): 20 parts Initiator Omnirad184 (IGM RESINS BV): 2.0 parts by weight Next, methyl ethyl ketone (hereinafter referred to as MEK) was added so that the total solid content ratio became 60 mass %, and then the mixture was mixed by stirring with a motor to prepare an electrolyte solution.
[0147] (Measurement of volume swelling ratio by MEK immersion method) The test pieces for the volume swelling ratio by MEK immersion method were prepared as follows using the electrolyte solution of each Example. A predetermined amount of the surface layer forming dispersion of each Example was added to an aluminum mold with a fluororesin coating on the surface to give a film thickness of 200 μm. Then, the sample was placed on a sunflower stand and dried until the viscosity increased to the extent that the surface of the film did not flow, and then the sample was placed on a horizontal stand and dried at 60° C. for 2 hours. Next, a high-pressure mercury UV irradiation device (product name: Handy 1000, manufactured by Mario Network) was used to irradiate the UV light with an integrated dose of 5000 mJ / cm in air. 2 The membrane surface was irradiated with UV light so that the polymer electrolyte was cross-linked and cured. After curing, the electrolyte membrane was left in an environment of 23°C and 40% RH for 24 hours, and then peeled off from the aluminum mold to prepare a sheet with a thickness of 200 μm. The obtained polymer electrolyte sheet was cut into a size of 50 mm x 50 mm and left in an environment of 23°C and 40% RH for 24 hours to prepare a test piece.
[0148] First, the initial weight in air (W1) and the initial weight in water (W2) were measured in an environment of 23°C and 40% humidity. Next, the test piece after the initial weight measurement was immersed in MEK at 23°C for 48 hours. Immediately after removing the test piece from MEK, the MEK on the surface was wiped off with a nonwoven fabric, and the test piece was placed in a weighing bottle that had been weighed in advance, and the weight after immersion in air (W3) and the weight after immersion in water (W4) were measured. The volume swelling ratio after immersion in MEK was calculated using the following formula. Volume swelling rate (%) = ((W3-W4)-(W1-W2)) / (W1-W2) x 100 W1: Initial weight in air W2: Initial weight in water W3: Weight after immersion in air W4: Weight after immersion in water
[0149] (Ionic conductivity measurement at room temperature (25℃)) The electrolyte solution obtained in Example 1 was applied to an aluminum plate having a thickness of 100 μm using a bar coater, and dried for 30 minutes at 60° C. Next, a high-pressure mercury UV irradiation device (product name: Handy 1000, manufactured by Mario Network Co., Ltd.) was used to apply an accumulated light amount of 5000 mJ / cm 2 The membrane surface was irradiated with UV light so as to crosslink and cure the polymer electrolyte membrane of Example 1. The membrane thickness after curing was 60 μm.
[0150] The obtained polymer electrolyte membrane was punched out together with the aluminum substrate to a diameter of 50 mm, and vacuum dried at 80°C for 48 hours. The polymer electrolyte membrane was then placed in an argon-substituted glove box (temperature 25°C, dew point -70°C), and the AC impedance between the electrodes was measured using an impedance analyzer E4990A (manufactured by KEYSIGHT) at an applied voltage of 10 mV and a frequency range of 100 MHz to 1 Hz. The bulk resistance value R was calculated from the real impedance intercept of the obtained Cole-Cole plot. B (Ω) was measured, and the ionic conductivity was calculated using the following formula. σ=L / R B ×S (σ: ionic conductivity (S cm -1 ), L: sample thickness (cm), S: sample area (cm 2 ))
[0151] (Ionic conductivity measurement at low temperature (5℃)) A polymer electrolyte membrane was obtained by forming it on an aluminum plate in the same manner as in the measurement of ionic conductivity at room temperature. The polymer electrolyte membrane was then placed in an argon-substituted glove box (temperature 25°C, dew point -70°C) and incorporated into an all-solid-state battery evaluation cell (manufactured by Hosensha). The evaluation cell incorporating the polymer electrolyte membrane was placed in a low-temperature environment tester and left for 1 hour at 5° C. Thereafter, the ionic conductivity at low temperature was determined in the same manner as above.
[0152] <Preparation of secondary battery> 1. Configuration using the polymer electrolyte of the present disclosure as the bulk electrolyte (Preparation of negative electrode) A 20mm x 20mm, 60μm thick lithium foil (manufactured by Honjo Metals) was laminated on a 20mm x 30mm, 20μm thick copper foil, leaving a 10mm non-laminated end on one side, and then pressed to produce a negative electrode. The total thickness of the negative electrode was 70μm. A 5mm wide copper tab with nickel plating on one non-laminated end on one side was joined to the negative electrode.
[0153] (Preparation of positive electrode) 100 parts by mass of lithium cobalt oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was mixed with 7 parts by mass of Kureha KF Polymer L#1120 (manufactured by Kureha Corporation) as an active material binder, and 5 parts by mass of Denka Black Li-100 (manufactured by Denka Corporation) as a conductive assistant, and 40 parts by mass of N-methylpyrrolidone was added and mixed and stirred. Next, the obtained slurry was coated on a rolled aluminum foil of 15 mm x 25 mm and 20 μm in thickness, leaving a 10 mm uncoated end on one side, and then dried at 100 ° C for 30 minutes and pressed to obtain a positive electrode. The thickness of the positive electrode was 80 μm. An aluminum tab having a width of 5 mm was attached to one uncoated end of the positive electrode.
[0154] (Formation of polymer electrolyte layer) An electrolyte solution was applied to the entire active material-coated surface of the obtained positive electrode using a bar coater, and the positive electrode was air-dried for 10 minutes at 23° C., and then dried for 30 minutes at 60° C. Next, a high-pressure mercury UV irradiation device (product name: Handy 1000, manufactured by Mario Network Co., Ltd.) was used to apply an accumulated light amount of 5000 mJ / cm 2 The film surface was irradiated with UV light and cured so that the film thickness after curing was 60 μm.
[0155] (Preparation of secondary batteries using polymer electrolyte as bulk electrolyte) The positive electrode coated with the polymer electrolyte was vacuum dried at 80°C for 48 hours. The polymer electrolyte film was then placed in an argon-substituted glove box (temperature 25°C, dew point -70°C), and a polyimide sheet punched into a window frame shape was attached to cover the outer periphery of the positive electrode surface to form a short-circuit prevention layer. Next, the polymer electrolyte layer of the positive electrode coated with the polymer electrolyte was laminated so as to correspond to the lithium layer of the negative electrode. The laminate was sandwiched between aluminum laminate films and vacuum-packed to obtain a secondary battery according to Example 1.
[0156] <Battery characteristic evaluation> (Rate characteristics) The theoretical capacity was calculated from the total mass of lithium cobalt oxide contained in the positive electrode. A charge / discharge test was performed on the prototype secondary battery at 25°C using a charge / discharge device BCS-805 (manufactured by BioLogic Corporation). The theoretical capacity was calculated from the total mass of lithium cobalt oxide contained in the positive electrode. Charge at a constant current of 0.05C, with a cutoff value of 3.9V for 2 hours. The battery was discharged at a constant current of 0.05C with a cutoff voltage of 2.0V for 1 hour. Next, the charge and discharge rates were increased by 0.05C each time, and the same charge and discharge were performed. The rate at which the charge and discharge could be performed without exceeding the cutoff value was taken as the rate characteristic.
[0157] (Strength evaluation at high temperatures) The prototype secondary batteries were subjected to impact once in an environment of 25°C using a thin film impact tester QC-633 (manufactured by Cometech Testing Machines) with an impact tip diameter of Φ38.1 mm, a load of 120 g, a height of 150 mm, and a tester to perform a short circuit test on the batteries. Five batteries were prototyped for each example, and the impact test was performed five times in total, and the number of batteries that shorted out was counted. Next, the impact tester and secondary battery were placed in an environmental tester set at 60°C, and after leaving them for two hours, the same test was performed and the number of batteries that experienced a short circuit during the high temperature test was counted.
[0158] (Short circuit occurrence evaluation) The prototype secondary battery was repeatedly charged and discharged in an environment of 40°C. The battery was charged at a charge rate of 0.05C and a charge voltage of 4.0V, and discharged at a discharge rate of 0.05C and a discharge voltage of 3.0V. The number of cycles until abnormal voltage behavior occurred during charging and discharging was counted.
[0159] Next, the electrodes were removed from the batteries after evaluation, and the surfaces were observed with a digital microscope VHX-5000 (manufactured by Keyence Corporation) at 50x and 500x objective lenses to see if there were dendrites (dendrites) on the surfaces.
[0160] [Examples 2 to 32] The polymer electrolytes and secondary batteries according to Examples 2 to 32 were prepared in the same manner as in Example 1, except that the types and amounts of polyether mono(meth)acrylate, polyether di(meth)acrylate, ionic compound, and supporting electrolyte were changed as shown in Table 3.
[0161] [Table 3]
[0162] The structures of the materials used when polymerized are as follows: M-230G (methoxypolyethylene glycol methacrylate, in which R1 in formula (1-1) is a methyl group and R2 is an ethylene group -(CH 2 ) 2 -, R3: methyl group, m1: 23, n1: 0) AM-130G (methoxypolyethylene glycol #600 acrylate, in formula (1-1) R1: hydrogen atom, R2: ethylene group, R3: methyl group, m1: 13, n1: 0) AM-230G (methoxypolyethylene glycol #1000 acrylate, in formula (1-1) R1: hydrogen atom, R2: ethylene group, R3: methyl group, m1: 23, n1: 0) AM-90G (methoxypolyethylene glycol #400 acrylate, in formula (1-1), R1: hydrogen atom, R2: ethylene group, R3: methyl group, m1: 9, n1: 0) M-450G (methoxypolyethylene glycol methacrylate, in the formula (1-1) R1: methyl group, R2: ethylene group, R3: methyl group, m1: 45, n1: 0)
[0163] A-1000PER (in formula (2-1), R4 is a hydrogen atom, R5 is an ethylene group or a propylene group, R6 is an ethylene group or a propylene group, m2 is 17, and n2 is 4) A-1000 (polyethylene glycol #1000 diacrylate, in formula (2-1), R4: hydrogen atom, R5: ethylene group, R6: ethylene group, m2: 23, n2: 0) A-400 (polyethylene glycol #400 diacrylate, in formula (2-1), R4: hydrogen atom, R5: ethylene group, R6: ethylene group, m2: 9, n2: 0) A-600 (polyethylene glycol #600 diacrylate, in formula (2-1), R4: hydrogen atom, R5: ethylene group, R6: ethylene group, m2: 14, n2: 0)
[0164] A-GLY-20E (ethoxylated glycerin triacrylate, in formula (3-1), R7: hydrogen atom, R8: ethylene group, R9: ethylene group, R10: ethylene group, R11: -CH2(CH-)CH2-, m3: 20 as the total of formula (3-1), n3: 0) 9G: polyethylene glycol #400 dimethacrylate (in formula (2-1), R4 is a methyl group, R5 is an ethylene group, R6 is an ethylene group, m2 is 9, n2 is 0) 14G: polyethylene glycol #600 dimethacrylate (in formula (2-1), R4 is a methyl group, R5 is an ethylene group, R6 is an ethylene group, m2 is 14, n2 is 0) All of the above are manufactured by Shin-Nakamura Chemical Co., Ltd.
[0165] MEMA-4000: (Polyethylene glycol #4000 dimethacrylate (R4: methyl group, R5: ethylene group, R6: ethylene group, m2: 90, n2: 0 in formula (2-1)) manufactured by Toho Chemical Industry Co., Ltd. PEGDA-4000: (polyethylene glycol diacrylate, in formula (2-1), R4: hydrogen atom, R5: ethylene group, R6: ethylene group, m2: 90, n2: 0) manufactured by Techno Chemical Co., Ltd.
[0166] Li·TFSI stands for lithium bis(trifluoromethanesulfonyl)imide. Li·FSI stands for lithium bis(fluorosulfonyl)imide. Li·PF6 stands for (lithium hexafluorophosphate).
[0167] 2. Configuration using the polymer electrolyte of the present disclosure as a positive electrode active material binder [Example 33] (Preparation of negative electrode) A 20mm x 20mm, 60μm thick lithium foil (manufactured by Honjo Metals) was laminated on a 20mm x 30mm, 20μm thick copper foil, leaving a 10mm non-laminated end on one side, and then pressed to produce a negative electrode. The total thickness of the negative electrode was 70μm. A 5mm wide copper tab with nickel plating on one non-laminated end on one side was joined to the negative electrode.
[0168] (solid electrolyte) A LICGC (manufactured by Ohara Corporation) sheet measuring 20 mm x 20 mm and having a thickness of 0.18 mm was used.
[0169] (Preparation of positive electrode) 100 parts by mass of lithium cobalt oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was mixed with 18 parts by mass of the electrolyte solution (solid content 60%) of Example 1 as an active material binder and 5 parts by mass of Denka Black Li-100 (manufactured by Denka Co., Ltd.) as a conductive assistant, and 40 parts by mass of N-methylpyrrolidone was added and mixed and stirred. Next, the obtained slurry was coated onto a rolled aluminum foil of 15 mm x 25 mm and 20 μm in thickness, leaving a 10 mm uncoated edge on one side, and then dried at 100° C. for 30 minutes, followed by heating with a high-pressure mercury UV irradiation device (product name: Handy 1000, manufactured by Mario Network Co., Ltd.). ) with an accumulated light dose of 7000mJ / cm 2The film surface was irradiated with UV light to cure so that the thickness of the film was 80 μm. After curing, the film was pressed to obtain a positive electrode with a thickness of 80 μm. A 5 mm-wide aluminum tab was attached to the non-coated end of the positive electrode.
[0170] (Preparation of secondary batteries using polymer electrolyte as positive electrode active material binder) The positive electrode with the polymer electrolyte as the active material binder was vacuum dried at 80° C. for 48 hours. The polymer electrolyte membrane was then placed in an argon-substituted glove box (temperature 25° C., dew point −70° C.) and laminated in the order of positive electrode / solid electrolyte / negative electrode. The laminate was sandwiched between aluminum laminate films and vacuum-packed to obtain a secondary battery using the polymer electrolyte of the present disclosure as a positive electrode active material binder according to Example 33.
[0171] [Examples 34 to 36] Secondary batteries according to Examples 34 to 36 were produced in the same manner as in Example 33, except that the electrolyte solution (polymer electrolyte) was changed as shown in Table 7. Table 7 shows the evaluation results of the rate characteristics and the like.
[0172] 3. Configuration using the polymer electrolyte of the present disclosure as a bulk electrolyte, a positive electrode active material binder, and a negative electrode active material binder [Example 37] (Preparation of negative electrode) 100 parts by mass of graphite powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was mixed with 20 parts by mass of the electrolyte solution (60% solids) of Example 1 as an active material binder and 5 parts by mass of Denka Black Li-100 (manufactured by Denka Co., Ltd.) as a conductive assistant, and 80 parts by mass of N-methylpyrrolidone was added and mixed and stirred. Next, the obtained slurry was coated on a copper foil measuring 20 mm x 30 mm and 20 μm in thickness, leaving a 10 mm uncoated end on one side, and then dried at 100° C. for 30 minutes. Then, the coating was performed using a high-pressure mercury UV irradiation device (product name: Handy 1000, manufactured by Mario Network Co., Ltd.) with an accumulated light dose of 8000 mJ / cm. 2The film surface was irradiated with UV light to cure so that the film surface was cured. After curing, the film was pressed to obtain a negative electrode with a thickness of 80 μm. Negative electrode active material non-coated areas, where no negative electrode active material was coated on either side, were provided at both ends, and a 5 mm wide nickel-plated copper current collecting tab was joined to one of the negative electrode active material non-coated areas.
[0173] (Preparation of positive electrode) 100 parts by mass of lithium cobalt oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was mixed with 18 parts by mass of the electrolyte solution (solid content 60%) of Example 1 as an active material binder and 5 parts by mass of Denka Black Li-100 (manufactured by Denka Co., Ltd.) as a conductive assistant, and 40 parts by mass of N-methylpyrrolidone was added and mixed and stirred. Next, the obtained slurry was coated on a rolled aluminum foil with a thickness of 20 μm, dried at 60° C. for 30 minutes, and then irradiated with a high-pressure mercury UV irradiation device (product name: Handy 1000, manufactured by Mario Network Co., Ltd.) with an accumulated light amount of 7000 mJ / cm. 2 The film surface was irradiated with UV light to cure so that the film surface was cured. After curing, the film was pressed to obtain a positive electrode with a thickness of 80 μm. Neither side of the positive electrode active material was coated on either end of the film, and a 5 mm-wide aluminum current collector tab was joined to one of the positive electrode active material non-coated parts.
[0174] (Formation of polymer electrolyte layer) The electrolyte solution of Example 1 was applied to the obtained positive electrode using a bar coater, and the positive electrode was air-dried at 23° C. for 10 minutes, and then dried at 60° C. for 30 minutes. Next, a high-pressure mercury UV irradiation device (product name: Handy 1000, manufactured by Mario Network Co., Ltd.) was used to irradiate the positive electrode with an accumulated light amount of 5000 mJ / cm 2 . 2 The film surface was irradiated with UV light and cured so that the film thickness after curing was 60 μm.
[0175] (Preparation of secondary batteries using polymer electrolytes as bulk electrolyte, positive electrode active material binder, and negative electrode active material binder) The positive electrode and the negative electrode coated with the polymer electrolyte were vacuum dried at 80°C for 48 hours. Then, the polymer electrolyte film was placed in an argon-substituted glove box (temperature 25°C, dew point -70°C), and a polyimide sheet punched into a window frame shape was attached to cover the outer periphery of the positive electrode surface to form a short-circuit prevention layer. Next, the polymer electrolyte layer of the positive electrode coated with the polymer electrolyte and the active material layer of the negative electrode were laminated so as to correspond to each other. The laminate was sandwiched between aluminum laminate films and vacuum-packed to obtain a secondary battery using the polymer electrolyte of the present disclosure as the bulk electrolyte, positive electrode active material binder, and negative electrode active material binder according to Example 37.
[0176] [Examples 38 to 40] Secondary batteries according to Examples 38 to 40 were produced in the same manner as in Example 37, except that the electrolyte solution (polymer electrolyte) was changed as shown in Table 7. Table 7 shows the evaluation results of the rate characteristics and the like.
[0177] <Comparative Example> [Comparative Example 1] As materials for the polymer electrolyte, the following materials were mixed and stirred. Polyether monomethacrylate NK-Ester M-40G (manufactured by Shin-Nakamura Chemical Co., Ltd.): 70 parts by weight Polyether dimethacrylate 4G (manufactured by Shin-Nakamura Chemical Co., Ltd.): 30 parts by weight Lithium bis(trifluoromethanesulfonyl)imide (Kishida Chemical: 10.0 parts by mass) Initiator Omnirad184 (manufactured by IGM RESINS BV): 2.0 parts by weight Next, methyl ethyl ketone was added so that the total solid content ratio became 60% by mass, and then the mixture was mixed by stirring with a motor to prepare an electrolyte solution. Thereafter, in the same manner as in Example 1, a polymer electrolyte and a secondary battery according to Comparative Example 1 were produced.
[0178] [Comparative Examples 2 to 6] Polymer electrolytes and secondary batteries according to Comparative Examples 2 to 6 were prepared in the same manner as in Example 1, except that the types and amounts of polyether mono(meth)acrylate, polyether di(meth)acrylate, ionic compound, and supporting electrolyte were changed as shown in Table 4.
[0179] The secondary batteries of Comparative Examples 1 to 6 were configured to use a polymer electrolyte as a bulk electrolyte. Table 6 shows the evaluation results of the rate characteristics and the like.
[0180] [Table 4] The structures of the materials used when polymerized are as follows: M-40G: Methoxytetraethylene glycol methacrylate (in the formula (1-1) R1: methyl group, R2: ethylene group, R3: methyl group, m1: 3, n1: 0 4G: polyethylene glycol #200 dimethacrylate (R4 in formula (2-1): methyl group, R5: ethylene group, R6: ethylene group, m2: 4, n2: 0) APG-400: polypropylene glycol #400 diacrylate (in formula (2-1), R4 is a hydrogen atom, R5 is a propylene group, R6 is a propylene group, m2 is 0, n2 is 7) AM-90G, AM-130G, and A-600 are as described above. All of the above are manufactured by Shin-Nakamura Chemical Co., Ltd. PA-500: Hydroxypolypropylene glycol monoacrylate (in formula (1-1), R1 is a hydrogen atom, R2 is a propylene group, R3 is a hydroxyl group, m1 is 0, n1 is 5), manufactured by Toho Chemical Industry Co., Ltd.
[0181] [Comparative Example 7] The positive electrode active material binder was 7 parts by mass of Kureha KF Polymer L#1120 (manufactured by Kureha Corporation). A secondary battery according to Comparative Example 7 was produced in the same manner as in Example 33, except that the above-mentioned was used.
[0182] [Comparative Examples 8 to 10] Secondary batteries according to Comparative Examples 8 to 10 were fabricated in the same manner as in Example 33, except that the types and amounts of polyether mono(meth)acrylate, polyether di(meth)acrylate, ionic compound, and supporting electrolyte were changed as shown in Table 8. The secondary batteries of Comparative Examples 7 to 10 were configured using a polymer electrolyte as a binder for the positive electrode active material. Table 8 shows the evaluation results of the rate characteristics and the like.
[0183] [Comparative Examples 11 to 14] Secondary batteries according to Comparative Examples 11 to 14 were fabricated in the same manner as in Example 37, except that the types and amounts of polyether mono(meth)acrylate, polyether di(meth)acrylate, ionic compound, and supporting electrolyte were changed as shown in Table 8. The secondary batteries of Comparative Examples 11 to 14 were configured using a polymer electrolyte as a positive electrode active material binder, a bulk electrolyte, and a negative electrode active material binder. Table 8 shows the evaluation results of rate characteristics and the like.
[0184] The obtained polymer electrolytes and secondary batteries according to Examples 1 to 40 and Comparative Examples 1 to 14 were evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 5-1, 5-2, 6, 7 and 8.
[0185] [Table 5-1]
[0186] [Table 5-2] In Tables 5-1, 5-2 and 6, Mpo% is the ratio of the average number of moles added Mpo to the average number of moles added Meo.
[0187] [Table 6]
[0188] The polymer electrolytes according to Examples 1 to 32 have the structure of formula (4) in addition to the structure of formula (1) and at least one of the structures of formulas (2) and (3) in the polymer structure, and have a volume swelling ratio of 30 to 120%. Therefore, they show high ionic conductivity at both 25° C. and 5° C. Furthermore, the secondary batteries using the polymer electrolytes according to Examples 1 to 32 as bulk electrolytes have both high rate characteristics and high impact resistance at high temperatures. Furthermore, the polymer electrolytes according to Examples 1 to 32 have a volume swelling ratio of 30 to 120%, and in addition, A / (A+B) is 0.50 or more, so that the number of cycles until a short circuit occurs is large, resulting in a long-life secondary battery.
[0189] Furthermore, examples including Example 7 in which the mass ratio α:β of the content A of the structure of formula (1) to the content B of formula (2) in the polymer structure was 70:30 to 98:2, m1+n1 in formula (1-1) was 14 to 58, and m2+n2 in formula (2-1) was 14 to 58 showed particularly high ionic conductivity and the rate characteristics of the secondary battery were also good.
[0190] On the other hand, the polymer electrolytes according to Comparative Example 1, which does not have the structure of formula (4) in the polymer structure, Comparative Examples 2 and 6, which do not have the structure of formula (1), and Comparative Example 3, which has a volume swelling ratio of less than 30%, had low ionic conductivity and very poor rate characteristics as secondary batteries. In Comparative Examples 2 to 6, in which A / (A+B) is less than 0.50, the number of cycles until a short circuit occurred was also small, and dendrites were observed on the surface of the battery electrode.
[0191] Moreover, the secondary batteries using the polymer electrolytes according to Comparative Examples 4 and 5, which had a volume swelling rate of more than 120% or had no three-dimensional cross-linking, showed a significant decrease in impact resistance at high temperatures.
[0192] [Table 7]
[0193] [Table 8]
[0194] The secondary batteries according to Examples 33 to 36 in which the polymer electrolyte of the present disclosure is used as a positive electrode active material binder, and the secondary batteries according to Examples 37 to 40 in which the polymer electrolyte is used as a positive electrode active material binder, bulk electrolyte, or negative electrode active material binder, have both high rate characteristics and high impact resistance at high temperatures, similar to the case in which the polymer electrolyte is used as a bulk electrolyte.
[0195] On the other hand, the secondary batteries according to Comparative Examples 8 and 11, which did not have the structure of Formula (4) in the polymer structure, Comparative Examples 9 and 10, which did not have the structure of Formula (1), and Comparative Example 12, which had a volume swelling ratio of less than 30%, showed poor rate characteristics. Also, the secondary batteries according to Comparative Examples 13 and 14, which had a volume swelling ratio of more than 120 or did not have three-dimensional crosslinks, showed a significant decrease in impact resistance at high temperatures.
[0196] The present disclosure has the following configuration. (Configuration 1) A polymer electrolyte comprising: The polymer electrolyte includes a polymer and an alkali metal salt, The alkali metal salt is at least one selected from the group consisting of bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and hexafluorophosphate. Contains an alkali metal salt as the anion, The polymer is A structure represented by the following formula (1), At least one structure selected from the group consisting of a structure represented by the following formula (2) and a structure represented by the following formula (3), and a structure represented by the following formula (4): When the total number of moles of the anions in the alkali metal salt contained per unit mass of the polymer electrolyte is A and the number of moles of the sulfonylimide groups bonded to the polymer is B, A and B satisfy the relationship of the following formula (X): 0.50≦A / (A+B) (X) The polymer electrolyte further comprises a polymer electrolyte having a volume swelling ratio of 30 to 120% as measured by a methyl ethyl ketone immersion method. TIFF2025023821000026.tif187168 (In formula (1), R 1 R represents a hydrogen atom or a methyl group. 2 R represents a linear or branched alkylene group having 1 to 6 carbon atoms. 3 represents an alkyl group having 1 to 6 carbon atoms. In formula (2), R 4 R each independently represents a hydrogen atom or a methyl group. 5 and R 6 each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. In formula (3), R 7 R each independently represents a hydrogen atom or a methyl group. 8 , R 9 and R 10 R each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. 11 represents a trivalent organic group having 1 to 6 carbon atoms. In the formulas (1) to (3), A1, B1, D1, D2 and D3 each independently represent at least (-CH 2 CH 2 It is a linking group having an ethylene oxide structure represented by the formula: TIFF2025023821000027.tif57168 (In formula (4), R 12 R represents a hydrogen atom or a methyl group. 13 R represents a divalent linking group. 14 represents a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms. + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion. The sulfonylimide group is a functional group represented by the following formula (S). TIFF2025023821000028.tif40168 In formula (S), R represents a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms. (Configuration 2) The polymer electrolyte according to configuration 1, wherein A and B satisfy 0.65≦A / (A+B)≦0.96. (Configuration 3) 3. The polymer electrolyte according to claim 1, wherein an average number of moles Meo of the ethylene oxide structure added per mole of the (meth)acryloyl residue in the polymer is 2.5 moles or more. (Configuration 4) A1, B1, D1, D2 and D3 each independently represent (-CH 2 CH(CH 3 The polymer according to any one of the configurations 1 to 3, further having a propylene oxide structure represented by the formula: -Electrolytes. (Configuration 5) 5. The polymer electrolyte according to claim 4, wherein in the polymer, an average number of moles Mpo of the propylene oxide structure added per mole of the (meth)acryloyl residue is 5 to 25% of an average number of moles Meo of the ethylene oxide structure added per mole of the (meth)acryloyl residue. (Configuration 6) The polymer electrolyte according to any one of configurations 1 to 5, wherein a mass ratio of the structure represented by formula (1) in the polymer contained in the polymer electrolyte is α and a total mass ratio of the structure represented by formula (2) and the structure represented by formula (3) is β, and the mass ratio of the structure represented by formula (2) and the structure represented by formula (3) is 70:30 to 98:2. (Configuration 7) The structure represented by the formula (1) is a structure represented by the following formula (1-1): The structure represented by the formula (2) is a structure represented by the following formula (2-1): The structure represented by the formula (3) is a structure represented by the following formula (3-1): 7. The polymer electrolyte according to any one of aspects 1 to 6. TIFF2025023821000029.tif46168 (In formula (1-1), R1 R represents a hydrogen atom or a methyl group. 2 R represents a linear or branched alkylene group having 1 to 6 carbon atoms. 3 represents an alkyl group having 1 to 6 carbon atoms. m1 and n1 are the average number of moles added, m1 represents an integer of 1 or more, and n1 represents an integer of 0 or more. (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the propylene oxide structure represented by -O- may be a block copolymer or a random copolymer. TIFF2025023821000030.tif46168 (In formula (2-1), R 4 R each independently represents a hydrogen atom or a methyl group. 5 , R 6 each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. m2 and n2 represent the average number of moles added, m2 represents an integer of 1 or more, and n2 represents an integer of 0 or more. (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the propylene oxide structure represented by (a)-O-) may be a block copolymer. However, it may be a random copolymer. The chain sandwiched between two -COO- may further contain a diol structure having 1 to 6 carbon atoms. TIFF2025023821000031.tif70168 (In formula (3-1), R 7 R each independently represents a hydrogen atom or a methyl group. 8 , R 9 , R 10 R each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. 11represents a trivalent organic group having 1 to 6 carbon atoms. m3 and n3 are the average number of moles added, each m3 independently represents an integer of 1 or more, and each n3 independently represents an integer of 0 or more. (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the propylene oxide structure represented by -O-) may be a block copolymer or a random copolymer. The chain sandwiched between -COO- and R11 may further contain a diol structure having 1 to 6 carbon atoms. (Configuration 8) In the polymer electrolyte, m1+n1 in the formula (1-1) is 14 to 58, 8. The polymer electrolyte according to claim 7, wherein m2+n2 in the formula (2-1) and / or m3+n3 in the formula (3-1) is 14 to 58. (Configuration 9) In the polymer electrolyte, In the formula (1-1), m1:n1 is 80:20 to 95:5; 9. The polymer electrolyte according to aspect 7 or 8, wherein m2:n2 in the formula (2-1) and / or m3:n3 in the formula (3-1) is 80:20 to 95:5. (Configuration 10) 10. The polymer electrolyte according to any one of configurations 1 to 9, wherein the content of the structure represented by formula (4) in the polymer electrolyte is 1 to 25 parts by mass per 100 parts by mass in total of the structure represented by formula (1), the structure represented by formula (2), and the structure represented by formula (3). (Configuration 11) 11. The polymer electrolyte according to any one of configurations 1 to 10, wherein the polymer electrolyte is a dry polymer electrolyte. (Configuration 12) A secondary battery comprising a positive electrode, a bulk electrolyte, and a negative electrode, 12. A secondary battery, wherein at least one selected from the group consisting of the positive electrode, the bulk electrolyte, and the negative electrode contains the polymer electrolyte according to any one of configurations 1 to 11. (Configuration 13) A secondary battery comprising a positive electrode, a bulk electrolyte, and a negative electrode, The secondary battery is characterized by satisfying at least one of the following (i) to (iii): (i) The positive electrode has a positive electrode active material and a positive electrode active material binder that fixes the positive electrode active material, and the positive electrode active material binder is the polymer electrolyte according to any one of configurations 1 to 11. (ii) The bulk electrolyte is a polymer electrolyte according to any one of configurations 1 to 11. (iii) The negative electrode has a negative electrode active material and a negative electrode active material binder that fixes the negative electrode active material, and the negative electrode active material binder is the polymer electrolyte according to any one of Configurations 1 to 11. [Explanation of symbols]
[0197] 1: secondary battery, 2: positive electrode current collector, 3: positive electrode active material, 4: positive electrode active material binder, 5: conductive additive, 6: positive electrode, 7: bulk electrolyte, 8: negative electrode active material, 9: negative electrode current collector, 10: negative electrode, 11: negative electrode active material binder
Claims
1. A polymer electrolyte comprising: The polymer electrolyte includes a polymer and an alkali metal salt, The alkali metal salt includes an alkali metal salt having at least one anion selected from the group consisting of bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and hexafluorophosphate; The polymer is A structure represented by the following formula (1): At least one structure selected from the group consisting of a structure represented by the following formula (2) and a structure represented by the following formula (3), and a structure represented by the following formula (4): When the total number of moles of the anions in the alkali metal salt contained per unit mass of the polymer electrolyte is A and the number of moles of the sulfonylimide groups bonded to the polymer is B, A and B satisfy the relationship of the following formula (X): 0.50≦A / (A+B) ・・・(X) and wherein the polymer electrolyte has a volume swelling ratio of 30 to 120% as measured by a methyl ethyl ketone immersion method. (In formula (1), R 1 represents a hydrogen atom or a methyl group. 2 R represents a linear or branched alkylene group having 1 to 6 carbon atoms. 3 represents an alkyl group having 1 to 6 carbon atoms. In formula (2), R 4 R each independently represents a hydrogen atom or a methyl group. 5 and R 6 each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. In formula (3), R 7 R each independently represents a hydrogen atom or a methyl group. 8 , R 9 and R 10 R each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. 11 represents a trivalent organic group having 1 to 6 carbon atoms. In the formulas (1) to (3), A1, B1, D1, D2 and D3 each independently represent at least (-CH 2 CH 2 It is a linking group having an ethylene oxide structure represented by the formula: (In formula (4), R 12 represents a hydrogen atom or a methyl group. 13 represents a divalent linking group. 14 represents a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms. + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion. The sulfonylimide group is a functional group represented by the following formula (S). In formula (S), R represents a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms.
2. The polymer electrolyte according to claim 1 , wherein A and B satisfy 0.65≦A / (A+B)≦0.
96.
3. 2. The polymer electrolyte according to claim 1, wherein an average number of moles Meo of the ethylene oxide structure added per mole of the (meth)acryloyl residue in the polymer is 2.5 moles or more.
4. A1, B1, D1, D2 and D3 each independently represent (-CH 2 CH (CH 3 2. The polymer electrolyte according to claim 1, further comprising a propylene oxide structure represented by the formula:
5. 5. The polymer electrolyte according to claim 4, wherein in the polymer, an average number of moles Mpo of the propylene oxide structure added per mole of the (meth)acryloyl residue is 5 to 25% of an average number of moles Meo of the ethylene oxide structure added per mole of the (meth)acryloyl residue.
6. 2. The polymer electrolyte according to claim 1, wherein the mass ratio α:β is 70:30 to 98:2, where α is the mass content of the structure represented by formula (1) in the polymer contained in the polymer electrolyte, and β is the total mass content of the structure represented by formula (2) and the structure represented by formula (3).
7. The structure represented by the formula (1) is a structure represented by the following formula (1-1): The structure represented by the formula (2) is a structure represented by the following formula (2-1): The structure represented by the formula (3) is a structure represented by the following formula (3-1): The polymer electrolyte of claim 1 . (In formula (1-1), R 1 represents a hydrogen atom or a methyl group. 2 R represents a linear or branched alkylene group having 1 to 6 carbon atoms. 3 represents an alkyl group having 1 to 6 carbon atoms. m1 and n1 each represent the average number of moles added, where m1 represents an integer of 1 or more, and n1 represents an integer of 0 or more. (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the propylene oxide structure represented by the formula (I)-O-) may be a block copolymer or a random copolymer. (In formula (2-1), R 4 R each independently represents a hydrogen atom or a methyl group. 5 , R 6 each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms; m2 and n2 represent the average number of moles added, m2 represents an integer of 1 or more, and n2 represents an integer of 0 or more. (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the propylene oxide structure represented by -O-) may be a block copolymer or a random copolymer. The chain sandwiched between two -COO- may further contain a diol structure having 1 to 6 carbon atoms. (In formula (3-1), R 7 R each independently represents a hydrogen atom or a methyl group. 8 , R 9 , R 10 R each independently represents a linear or branched alkylene group having 1 to 6 carbon atoms. 11 represents a trivalent organic group having 1 to 6 carbon atoms. m3 and n3 are the average number of moles added, each m3 independently represents an integer of 1 or more, and each n3 independently represents an integer of 0 or more. (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the propylene oxide structure represented by -O-) may be a block copolymer or a random copolymer. The chain sandwiched between -COO- and R11 may further contain a diol structure having 1 to 6 carbon atoms.
8. In the polymer electrolyte, m1+n1 in the formula (1-1) is 14 to 58, The polymer electrolyte according to claim 7, wherein m2+n2 in the formula (2-1) and / or m3+n3 in the formula (3-1) is 14 to 58.
9. In the polymer electrolyte, In the formula (1-1), m1:n1 is 80:20 to 95:5; The polymer electrolyte according to claim 7, wherein m2:n2 in the formula (2-1) and / or m3:n3 in the formula (3-1) is 80:20 to 95:
5.
10. The polymer electrolyte according to claim 1, wherein the content of the structure represented by formula (4) in the polymer electrolyte is 1 to 25 parts by mass, relative to a total of 100 parts by mass of the structure represented by formula (1), the structure represented by formula (2), and the structure represented by formula (3).
11. The polymer electrolyte of claim 1 , wherein the polymer electrolyte is a dry polymer electrolyte.
12. A secondary battery comprising a positive electrode, a bulk electrolyte, and a negative electrode, A secondary battery, characterized in that at least one selected from the group consisting of the positive electrode, the bulk electrolyte, and the negative electrode contains the polymer electrolyte according to any one of claims 1 to 11.
13. A secondary battery comprising a positive electrode, a bulk electrolyte, and a negative electrode, The secondary battery is characterized in that it satisfies at least one of the following (i) to (iii): (i) The positive electrode has a positive electrode active material and a positive electrode active material binder that fixes the positive electrode active material, and the positive electrode active material binder is the polymer electrolyte according to any one of claims 1 to 11. (ii) The bulk electrolyte is the polymer electrolyte according to any one of claims 1 to 11. (iii) The negative electrode has a negative electrode active material and a negative electrode active material binder that fixes the negative electrode active material, and the negative electrode active material binder is the polymer electrolyte according to any one of claims 1 to 11.
Citation Information
Patent Citations
Dry polymer electrolyte, and all-solid polymer battery
JP2009104891A
Gel electrolyte and electrochromic device
JP2017090677A
Composition for polyelectrolytes, polyelectrolytes, electrical double layer capacitors and nonaqueous electrolyte secondary cells
WO2004027789A1